Prevalence of Covid-19 Awareness Among Physiotherapy Students of Punjab Pakistan - Anum, Sibgha; Shabbir, Nida; Abdeen, Zain Ul (MultiTech Publisher, 2024)
The Covid-19 outbreak has become a major concern for healthcare personnel. The purpose of this study was to look into the level of awareness about covid-19 illness and relevant preventative c measurements among Pakistani students studying physiotherapy in Punjab. This study was cross-sectional and observational. It was finished in Punjab, Pakistan, in ten months. After receiving approval for the summary, the investigation was finished in the expected three months. A non-probability handy sampling method was utilized. This study involved 384 physiotherapy students.Raosoft and SPSS was employed as a tool.It's time to use training programs to increase awareness among all physiotherapy students. In Punjab, Pakistan, 71.2 percent of physiotherapy students reported knowing about COVID-19. This indicates a reasonable understanding of Covid-19. The COVID-19 epidemic has This is an issue for healthcare workers. The The aim of this study was to find out how much knowledge physiotherapy students in Punjab, Pakistan, have about the Covid-19 virus and related prophylactic measures. This study was cross-sectional and observational. It was finished in Punjab, Pakistan, in ten months. After receiving approval for the summary, the investigation was finished in the expected three months. A non-probability handy sampling method was utilized. This study involved 384 physiotherapy students. Tools like Raosoft and SPSS were used.It's time to use training programs to increase awareness among all physiotherapy students. In Punjab, Pakistan, 71.2 percent of physiotherapy students reported knowing about COVID-19. This indicates a reasonable understanding of Covid-19